THE PSYCHOLOGICAL IMPACT OF ELECTROCARDIOGRAM SCREENING IN NATIONAL COLLEGIATE ATHLETIC ASSOCIATION ATHLETES. Issue 4 (1st February 2017) - Asif, Irfan; Annett, Scott; Ewing, Alex; Abdelfattah, Ramy; Rothmier, Justin; Harmon, Kimberly; Drezner, Jonathan
Abstract : Background: Cardiovascular screening is a means to prevent sudden cardiac death in athletes. The American Heart Association has raised concerns that false-positive electrocardiogram (ECG) screening may cause undue anxiety. Objective: Determine the psychological impact of false-positive ECG screening in NCAA athletes and to stratify experiences based on screening outcome, race, gender, sport, and division of play. Design: Prospective, multi-site investigation. Setting: Seven NCAA institutions. Patients (or Participants): 1192 student-athletes (55.4% male, median age 19 years, 80.4% Caucasian). Assessment of Risk Factors: Pre-participation screening with a standardized history, physical examination, and ECG. Main Outcome Measurements: Pre- and post-screen validated assessments for health attitudes, anxiety, and impact of screening on sport. Results: 96.8% of athletes had a normal cardiovascular screen (96.8%), 2.9% had a false-positive ECG, and 0.3% were diagnosed with a serious cardiac condition. Prior to screening, 4.5% worried about cardiac risk and 70.1% preferred knowing about an underlying condition, rather than play sports without this knowledge. There was no difference in anxiety described by athletes with a normal versus false-positive screen (p=0.369). Reported anxiety levels during screening also did not differ when analyzed by different gender, race, division of play, or sport. Athletes with normal and false-positive screens had similar levels of satisfaction (p=0.714) and would recommend ECG screening to other athletes at similar rates (p=0.322). Compared to athletes with a normal screen, athletes with false-positive results also reported feeling safer during competition (p>0.01). In contrast, athletes with false-positive screens were more concerned about the possibility of sports disqualification (p<0.001) and the potential for developing a future cardiac condition (p<0.001). Conclusions: False-positive results from ECG screening do not cause excessive anxiety in NCAA athletes. Further understanding of athlete experiences could better prepare the practicing physician on ways to counsel athletes with an abnormal ECG in order to address additional concerns.